Strengthening Women’s Rights In Law Through Supreme Court Number 3 Year 2017 Regulation In Divorce Cases In The Religious Court - Sunarsi, Dessy; Sumiyati, Sumiyati (Opción, 2019)
PERMA Number 3 of 2017 concerning Guidelines for Judging Women’s Cases Against the Law is a form of protection for women against all acts of discrim- ination and this can enrich the quantity and quality of the judges related to gender equality. This research used the juridical-empirical research method. The results of the study indicate that there is no difference between before the enactment of PERMA Number 3 of 2017 and before in the “Cerai Gugat” case. The judges have not optimally implemented PERMA Number 3 of 2017. There are 3 obstacles involved in implementing PERMA No. 3 of 2017: (1) the Judge’s consideration if the wife submits divorce papers to the husband by considering them nusyuz or rebellious in accordance with the rules of fiqh, (2) there is no optimisation of proof and (3) the husband is not present at the hearing processes, so the Judge has difficulty getting holistic information.